Green Human Resource Management (GHRM) and Corporate Sustainability Performance: A Strategic Management Approach - Salamah Utami (PT. AVID MEDIA INDONESIA, 2026)
Corporate sustainability has evolved from a peripheral corporate social responsibility initiative into a core strategic orientation embedded within organizational governance and performance systems. In this transformation, Green Human Resource Management (GHRM) has emerged as a critical enabler, yet its integration within strategic management architecture remains fragmented. This study aims to examine how GHRM influences corporate sustainability performance through a strategic management perspective. Using a quantitative explanatory design, data were collected from managers and sustainability officers in medium and large firms through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that GHRM significantly affects corporate sustainability performance both directly and indirectly through strategic management integration. The mediation results indicate that sustainability outcomes are strengthened when green HR practices are aligned with corporate strategy, governance mechanisms, and management control systems. The model demonstrates substantial explanatory power, confirming that strategic integration enhances the effectiveness of GHRM in achieving environmental, social, and economic performance. The study concludes that GHRM functions as a dynamic capability that supports sustained competitive advantage when embedded within the broader strategic framework of the organization.